2022
DOI: 10.3390/su14084682
|View full text |Cite
|
Sign up to set email alerts
|

Composted Sewage Sludge Application in a Sugarcane Seedling Nursery: Crop Nutritional Status, Productivity, and Technological Quality Implications

Abstract: Composted sewage sludge (CSS) contains large amounts of organic matter and nutrients and can be used as an organic fertilizer to improve growth, yield, and quality of sugarcane. However, there is a lack of information regarding the impact of CSS application on sugarcane seedling performance in nursery environments. A field study was conducted using a randomized complete block design to evaluate the development, nutritional status, productivity, and technological quality of sugarcane seedlings after CSS applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This fact demonstrated the ability of organic fertilizer to supply these micronutrients to the soil, except soil Cu concentration, which was reduced in the second year. Among the studied micronutrients, soil Zn concentration was increased at both of the evaluated depths, as also occurred in a study by Silva et al [26,27], who evaluated the changes in the chemical properties of the soil after CSS application in sugarcane cultivation in Cerrado soil. Several other studies reported that residual CSS improves soil fertility in terms of the supply of micronutrients, such as B, Cu, Fe, Mn, and Zn, in legume cultivation [23,25].…”
Section: Attributessupporting
confidence: 71%
See 1 more Smart Citation
“…This fact demonstrated the ability of organic fertilizer to supply these micronutrients to the soil, except soil Cu concentration, which was reduced in the second year. Among the studied micronutrients, soil Zn concentration was increased at both of the evaluated depths, as also occurred in a study by Silva et al [26,27], who evaluated the changes in the chemical properties of the soil after CSS application in sugarcane cultivation in Cerrado soil. Several other studies reported that residual CSS improves soil fertility in terms of the supply of micronutrients, such as B, Cu, Fe, Mn, and Zn, in legume cultivation [23,25].…”
Section: Attributessupporting
confidence: 71%
“…61 of 8 July 2020, it can be registered as a Class B organic fertilizer [21]. Recently, there has been evidence of the agronomic viability of using CSS as an organic fertilizer, especially for supplying P, N, and micronutrients [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The seeds used by the factory are adapted to environmental conditions to achieve optimal production. Providing the right amount of fertilizer and nutrients in nurseries can increase the productivity of the sugarcane itself (Silva et al, 2022).…”
Section: New Trends In Nurserymentioning
confidence: 99%
“…Composting has been used to stabilize organic matter and reduce the risks of heavy metals and pathogens, mainly aiming for continuous agricultural sludge recycling (Hargreaves et al, 2008;Wang et al, 2017a). Composted sewage sludge (CSS) as organic fertilizer can improve the chemical, physical, and biological properties of soil, in addition to preventing the contamination and degradation of water resources (Jakubus and Graczyk, 2020;Prates et al, 2020;Prates et al, 2022;Silva et al, 2022a, Silva et al, 2022b. Unlike SS, CSS is already considered a safe product for use in agriculture as it complies with Brazilian standards for registration of organic fertilizers (Brasil, 2020b), which establish maximum limits for heavy metals and pathogenic organisms in CCS.…”
Section: Introductionmentioning
confidence: 99%